2009
DOI: 10.1073/pnas.0911556106
|View full text |Cite
|
Sign up to set email alerts
|

GroEL/GroES cycling: ATP binds to an open ring before substrate protein favoring protein binding and production of the native state

Abstract: The GroEL/GroES reaction cycle involves steps of ATP and polypeptide binding to an open GroEL ring before the GroES encapsulation step that triggers productive folding in a sequestered chamber. The physiological order of addition of ATP and nonnative polypeptide, typically to the open trans ring of an asymmetrical GroEL/GroES/ ADP complex, has been unknown, although there have been assumptions that polypeptide binds first, allowing subsequent ATP-mediated movement of the GroEL apical domains to exert an action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…For example, recent work has suggested that non-native substrate protein can bind to the trans ring of an ATP bullet complex, an observation that conflicts with a central assumption of the standard reaction model (17). Other recent work has suggested that ADP release plays a central role in the reaction cycle (18,19), whereas still other studies have suggested that ATP binds to an open GroEL ring before non-native substrate protein (20). None of these observations are easily reconciled with the standard model of the GroEL reaction cycle.…”
mentioning
confidence: 75%
“…For example, recent work has suggested that non-native substrate protein can bind to the trans ring of an ATP bullet complex, an observation that conflicts with a central assumption of the standard reaction model (17). Other recent work has suggested that ADP release plays a central role in the reaction cycle (18,19), whereas still other studies have suggested that ATP binds to an open GroEL ring before non-native substrate protein (20). None of these observations are easily reconciled with the standard model of the GroEL reaction cycle.…”
mentioning
confidence: 75%
“…This complex facilitates protein folding by sequestering polypeptide chains in a compartment formed by a nucleotide-bound, sevenmembered homooligomeric GroEL ring and a seven-membered homooligomeric GroES ring. An additional GroEL ring, the trans ring, sits adjacent to and facing the cis (GroESbound) ring but bears a collapsed conformation, which is unable to bind GroES until ATP hydrolysis and the completion of the catalytic cycle (33)(34)(35).…”
mentioning
confidence: 99%
“…It was long suggested that substrate binding precedes ATP binding and that, with associated apical domain movements, ATP binding has a role in protein unfolding; movements of the apical domains to which the protein substrate is attached force protein unfolding [47]. New data nonetheless suggest that ATP binding is more rapid than substrate association, indicating that ATP might already be bound when the substrate protein interacts with GroEL [48]. ATP addition does not appear to enhance substrate protein stretching, which would occur in a forced unfolding mechanism [48].…”
Section: Substrate Associationmentioning
confidence: 98%
“…New data nonetheless suggest that ATP binding is more rapid than substrate association, indicating that ATP might already be bound when the substrate protein interacts with GroEL [48]. ATP addition does not appear to enhance substrate protein stretching, which would occur in a forced unfolding mechanism [48]. In contrast, the variety of The traditional model termed the ''bullet cycle'' assumes that only one folding chamber is active at a given time.…”
Section: Substrate Associationmentioning
confidence: 99%